How ESG affects companies’ business and cost of financing? - Savola, Tarmo Nestori (My University, 2024)
The popularity of responsible thinking has grown globally, and governments, legislation, shareholders, private investors, and financial institutions have started to demand responsibil-ity reports from companies. Private investors, in particular, have begun to focus on responsi-bility factors, such as how a company considers environmental impacts and employee well-being in its operations, rather than solely maximizing profit. The purpose of this thesis is to examine the impact of companies' Environmental, Social, and Governance (ESG) practices on their business operations and financing costs. The thesis aims to illustrate, with concrete examples, how companies benefit from investing in responsibility and achieving high ESG scores. It explores the history of ESG and how various factors such as legislation, environmental awareness, climate change, conflicts, and international coopera-tion have influenced the development and growing popularity of ESG. The research section of this thesis focuses on how a company's ESG scores affect its financing costs and whether a connection can be observed between high ESG scores and lower financing costs. Vastuullisen ajattelun suosio on kasvanut maailmanlaajuisesti ja valtiot, lainsäädäntö, osak-keenomistajat, yksityissijoittajat ja rahoituslaitokset ovat alkaneet vaatimaan yrityksiltä vas-tuullisuusraportteja. Etenkin yksityiset sijoittajat ovat alkaneet voiton maksimoinnin sijasta kiinnittää huomiota myös vastuullisuustekijöihin, kuten esimerkiksi siihen miten yritys huo-mioi toiminnassaan ympäristön ja yrityksen työntekijöiden hyvinvoinnin. Tämän opinnäytetyön tarkoituksena on tarkastella yritysten ympäristön, sosiaalisen yhteis-kuntavastuun ja hallinnointitapojen ” Environmental, Social ja Governance” (ESG) vaikutusta yrityksen liiketoimintaan ja sen rahoituskustannuksiin. Opinnäytetyö keskittyy havainnollis-tamaan konkreettisin esimerkein, miten yritysten liiketoiminta hyötyy siitä, kun yritys panos-taa vastuullisuuteen ja saavuttaa korkeita ESG vastuullisuustuloksia. Opinnäytetyössä käy-dään lävitse ESG historiaa ja sitä, miten eri muuttujat kuten lainsäädäntä, ympäristötietoi-suus, ilmastonmuutos, konfliktit ja kansainvälinen yhteistyö ovat vaikuttaneet ESG:n kehityk-seen ja suosion kasvuun. Tutkimusosiossa opinnäytetyö keskittyy siihen, miten yrityksen ESG lukemat vaikuttavat sen rahoituksen hintaan ja onko korkeilla ESG lukemilla ja halvemmalla rahoituskustannuksilla havaittavissa yhteyttä.
Keywords: business; finance; corporate responsibility; societal responsibility; environmental responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance